From Inaction to Restrictions: Changes in Lebanon's Policy Responses to Syrian Mass Refugee Movement - Zeynep Şahin Mencutek (University of Duisburg-Essen, Käte Hamburger Kolleg / Centre for Global Cooperation Research (KHK/GCR21), 2017)
Focusing on the case of Lebanon in which refugee concentration is the highest in the world relative to the population size, this paper aims to explore which factors shape initial policy preferences and changes over time in the first refugee destination countries. The paper specifically questions the policy responses of Lebanon to the Syrian refugee movement from 2012 to 2016, the motivations behind policies and the consequences of change. The paper argues that despite historically being a refugee receiving country, Lebanon has had neither structured border management, nor effective reception, protection and integration policies. Instead, it has largely adopted ad hoc policies for each refugee group. Through its response to the Syrian refugee movement in the initial years, Lebanon's inaction showed characteristics of policy paralysis, a situation in which the government was unable to create or implement policy programs. The government was only able to block undesirable policy options, such as the establishment of camps, and to implement few ad-hoc policies that overall exemplify inaction. However, since the end of 2014, inaction has been replaced by restrictive measures on border management and reception to dissuade Syrian refugees, while the creation of protection and integration policies has been avoided. Policy changes in border control and reception reflect the Lebanese state's recognition of a demographic challenge, its desire to appease growing negative public sentiment, to renegotiate its sovereignty vis-à-vis growing security challenges and to increase the involvement of international organizations (IOs) in refugee governance. On the other hand, Lebanon refrains from developing protection and integration measures due to a lack of capacity, ideational concerns pertaining to a delicate sectarian balance, as well as its historical experience with the protracted Palestinian refugee issue. The paper is based on qualitative research including case study evaluation, process tracing and policy ethnography. Data is drawn from the desk research of secondary literature, published reports and news as well as on fieldwork.
urn:nbn:de:hbz:464-20180110-150315-8
Keywords: 320; refugee governance; refugee policies; refugee hosting countries; Lebanon; Syrian mass flow; Syrian refugee movement; politics of refugees in Middle East